PENGUATAN LITERASI PEREMPUAN PADA KADER MASYARAKAT KOTA MOJOKERTO MELALUI PENERBITAN TABLOID SUHITA - Zahro, Aizatuz; Sidyawati, Lisa; Wardana, Ludi Wishnu; Subhan, -; Ningrum, Vira Setya (JURNAL WIDYA LAKSANA, 2021)
Strengthening women's literacy through the publishing of the Suhita tabloid was carried out for community activist in the Mojokerto city. Literacy strengthening is done to support their duties as community activist. The name Suhita is taken from the name of Dyah Suhita who is the queen of the Majapahit Kingdom. In strengthening this literacy the participants were equipped with various journalistic and writing techniques to support their oral competence. Learning activities carried out with the jigsaw adaptation strategy. Participants were divided into groups according to the type of writing and the writing assignments were changed at each meeting. Such learning makes the atmosphere of life learning because learners are treated as adults who are full of initiative and independence. The results of activities in the form of writings that are ready to be published because editing is also done together in each lesson. Editing was done in a new group. The new group is formed by the way the original group divides itself into new groups. Learning outcomes are published in a 16-page tabloid. Keywords: women's literacy, community cadres, Suhita